(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The incidence of peptic ulcer disease in Nigeria is 28% (Ndububa and Adeyemi, 2008). Clarithromycin (CLX) is used in the treatment of peptic ulcer owing to its antibacterial effect. Whether CLX has effects on other gastrointestinal parameters that reduce peptic ulcer has not been previously investigated. Therefore the effects of CLX on gastric acid secretion, mucus secretion and gastric ulcer scores in rats were investigated. A total of 30 albino wistar rats were used for the study. Out of this number, 10 rats each were used for gastric acid secretion, mucus secretion and ulcer scores respectively. In each of these sub groups, 5 rats served as test and were treated with CLX orally and 5 rats served as control. Standard methods were used for the estimation of these parameters of gastric function. The results showed that basal gastric acid, peak acid output following histamine stimulation and mucus secretion were significantly increased (p<0.001) in CLX-treated (test) rats than in their control. Furthermore, ulcer scores were significantly reduced (p<0.001) in the CLX-treated rats than control. In conclusion, Clarithromycin administration reduced gastric ulcers in rats. This may be attributable to not only its antibiotic property but also its ability to increase gastric mucus which counteracts the aggressive effect of the acid.